1999
DOI: 10.1116/1.590886
|View full text |Cite
|
Sign up to set email alerts
|

Si single-electron tunneling transistor with nanoscale floating dot stacked on a Coulomb island by self-aligned process

Abstract: Articles you may be interested inSingle-electron transistors based on self-assembled silicon-on-insulator quantum dots Si single electron tunneling transistor with nanoscale floating dot stacked on a Coulomb island by self-aligned process Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…The SET has been reported for many semiconductor materials, e.g. Si [2], III-V GaAs [6], carbon nanotubes [7,8], as well as metallic [9], and even ferromagnetic materials [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SET has been reported for many semiconductor materials, e.g. Si [2], III-V GaAs [6], carbon nanotubes [7,8], as well as metallic [9], and even ferromagnetic materials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A single-electron transistor (SET) exhibits Coulomb oscillation and quantized V th shifts which suggests the possibility of utilizing it as a memory device with ultralow power consumption [1,2]. Other application concepts have been exploited, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…146 A Si single electron transistor with a nanoscale floating dot gate stacked on a Coulomb island with potential memory applications was fabricated by Nakajima et a/. 147 ' 148 Metallic single electron devices using two different resist masks have been fabricated by Weimann et al U9 in a process that overcomes the problem of insulation of the edges by building a suspended island with no contact to the edges or with the substrate.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Figure 4 shows the calculated behavior of P(n) as a function of gate voltage V b for Tϭ77 K, nϭ1,2, and C ͚ ϭ1.3 aF ͑as obtained in our device͒, indicating that there are V g regions where the overlap in the electron number of two states has a relatively high probability. Nakajima et al 14 showed that for a particular temperature whether the overlap is weak or strong is controlled by C ͚ , which varies from device to device. Thus Fig.…”
mentioning
confidence: 99%
“…Another reason for this nonequilibrium memory state could be the electron number fluctuation in the dot as suggested by Nakajima et al 14 The probability P(n) that n electrons ͑with discrete charge͒ are stored can be expressed as…”
mentioning
confidence: 99%